2000
DOI: 10.1111/j.1530-0277.2000.tb04584.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Deficits in Sober Alcoholics: Influences of Chronicity and Recent Alcohol Consumption

Abstract: These data provide weak support for a dose effect relationship between degree of NP impairment and level of alcoholic drinking in the past 6 months but no evidence for an influence of chronicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(43 citation statements)
references
References 22 publications
5
37
1
Order By: Relevance
“…The cognitive domains which were the most impaired were visuospatial capacity, attention, language, abstraction and delayed recall, in accordance with other studies [3, 20, 38, 39]. …”
Section: Discussionsupporting
confidence: 92%
“…The cognitive domains which were the most impaired were visuospatial capacity, attention, language, abstraction and delayed recall, in accordance with other studies [3, 20, 38, 39]. …”
Section: Discussionsupporting
confidence: 92%
“…It is also noteworthy that, in this report, and in our earlier work (Durazzo et al, 2007c, 2008, 2010a) measures of alcohol consumption were not associated with neurocognition. This is consistent with other research that found measures of alcohol consumption quantity/frequency were weakly or not related to neurocognition (Schafer et al, 1991; Beatty et al, 1995, 2000; Eckardt et al, 1998; Horner et al, 1999; Sullivan et al, 2000). …”
Section: Discussionsupporting
confidence: 91%
“…The testing session included a modified version of the Acker battery (Acker and Acker, 1982) (Sternberg 1966(Sternberg ,1975, and Digit Symbol Test (Form A and B) (Beatty et al, 2000;Wechsler, 1981). For each test, both speed and accuracy were assessed and an efficiency ratio (accuracy/time) was derived.…”
Section: Methodsmentioning
confidence: 99%
“…On Form A, the subject was instructed to quickly fill in the empty spaces with the symbol that corresponds to the number within the allotted time frame of 90 sec. On Form B, (adapted for use in this laboratory, see Beatty et al, 2000) the subject was instructed to quickly fill in the empty spaces with the symbol that corresponds to the number plus one (an exception being the number nine, which requires "one's" symbol) for 90 sec. The number of squares filled in accurately is the score the subject received.…”
Section: Methodsmentioning
confidence: 99%